Dosing of glucocorticosteroids in nephrotic syndrome - Mehls, Otto; Hoyer, Peter F. (Pediatric nephrology, 2011)
Pharmacodynamic actions and molecular mechanisms of corticosteroids in patients with nephrotic syndrome (NS) are poorly understood. The role of immunosuppressive and of direct stabilizing effects on the podocyte cytoskeleton needs to be defined. Without precise knowledge of the pathogenesis, optimal dosing cannot be established. The finding of Saadeh et al. [1] that dosing of glucocorticoids per body surface area is superior to dosing per kilogram body weight (BW) in terms of reducing the recurrence rate of NS is interesting; however, an overriding effect of age cannot be ruled out. It is unlikely that all patients with an initial presentation of NS require the same amount of glucocorticoid treatment as patients with recurrent disease. In the future, it may be more important to establish individual treatment strategies than to adapt high doses of glucocorticoids according to anthropometric measurements.